Magnetic Material for Motor Drive Systems Fusion Technology of Electromagnetic Fields - Fujisaki, Keisuke; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on how to use magnetic material usefully for electrical motor drive system, especially electrical vehicles and power electronics. The contents have been selected in such a way that engineers in other fields might find some of the ideas difficult to grasp, but they can easily acquire a general or basic understanding of related concepts if they acquire even a rudimentary understanding of the selected contents. The cutting-edge technologies of magnetism are also explained. From the fundamental theory of magnetism to material, equipment, and applications, readers can understand the underlying concepts. Therefore, a new electric vehicle from the point of view of magnetic materials or a new magnetic material from the point of a view of electric vehicles can be envisioned: that is, magnetic material for motor drive systems based on fusion technology of an electromagnetic field. Magnetic material alone does not make up an electric vehicle, of course. Other components such as mechanical structure material, semiconductors, fuel cells, and electrically conductive material are important, and they are difficult to achieve. However, magnetic material involves one of the most important key technologies, and there are high expectations for its use in the future. It will be the future standard for motor-drive system researchers and of magnetic material researchers as well. This book is a first step in that direction.
Motor Drive System and Magnetic Material: Constitution of this book -- New Magnetic Material Requirement for Motor Drive System -- Magnetic Material -- Electrical Motor -- Power Electronics -- Electromagnetic Fusion Technology: Fusion of machine, application and material -- Magnetic Property excited by PWM Inverter -- Motor Core Loss Property Excited by Inverter -- Electrical Motor Applied by Low Iron Loss Magnetic Material -- Fundamental Theory for New Magnetic Material -- Magnetic Structure and Micromagnetics Calculation -- Polycristal Magnetic Modeling -- Magnetic Hysteresis Modeling by Play Model -- Magnetic Hysteresis Modeling by Thermo-Dynamic Model -- Equivalent Electrical Circuit Expression for High Frequency Electromagnetic Characteristics -- Combined Analysis Model of Power Semiconductor and Magnetic Characteristics -- Two-Dimensional Vector Magnetic Property -- Now and Future of Magnetic Material: Technical History of Magnetic Material and Permanent Magnet -- Low Loss Soft Magnetic Materials -- Sintered NdFeB Magnet -- Bonded NdFeB Magnet -- Rare Earth Problem for Permanent Magnets -- High Frequency Magnetic Characteristics -- Iron Loss Calculation of Electrical Motor -- Inductance Core Loss -- Magnetic Application for Automobile Car -- Magnetic Application in Linear Motor.
Keywords: Metals; Magnetism; Automotive engineering; Electric power production; Metals and Alloys; Magnetism; Automotive Engineering; Electrical Power Engineering